Development of in-service monitoring based models for remaining life management of thermally loaded ageing structures - Bonetti, Rossella (2025)
The primary aim of this thesis is to propose and develop a novel and practical life assessment methodology for power plant applications that uses more proactively both periodic and routine inspection data in conjunction with online operational data. This methodology facilitates the computation of the remaining life of high temperature components and essentially links the plant data routinely collected during outage inspections, via online monitoring or by testing of material samples to the life prediction models. High temperature pipework will be used as an example of the proposed approach and deployable creep life prediction models are reviewed that could function with these plant datasets. Of critical importance is that the output from the life prediction is used to inform plant operations on any necessary changes in order to mitigate damage accumulation.